ANALISIS TEKNIS DAN FINANSIAL AGROINDUSTRI SKALA KECIL PADA BERBAGAI PROSES PEMBUATAN KERIPIK TALAS DI KABUPATEN LAMPUNG BARAT - Ermayuli Ermayuli; Hanung Ismono; Sri Setyani (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2011)
Taro (Xanthosoma spp.) is widely grown in West Lampung area. The average productivity one 40 ton per hectare per year. The best technique to process taro crisp on a small scale in West Lampung regency, based on consumer preference, was Tiga Putra. If based on the yield, Kelompok Maju Tani was found the best, in addition , the traditional method was found more efficient if compared to semi-modern method. The analysis of financial showed that small scale talas crisp industry at West Lampung regency was considered to be feasible both processed using traditional and semi-modern methods. This was based on the fact that all criteria required for financial aspects met with positive results NPV, IRR resulting discount factor is greater than the bank discount factor, Pay back period (PP) is faster than the set time (10 years), and the Net B / C greater than 1 (one).